Bates' guide to physical examination and history taking (Philadelphia, PA : Wolters Kluwer, 2024)
For more than 40 years, Bates' Guide to Physical Examination and History Taking has been the singular authoritative source for students of medicine, nursing, and rehabilitation and others who are learning the skills of an effective, safe, and efficient patient clinical encounter. It also has been the preferred textbook of clinical skills program directors and educators in the United States.1 Since its inception by Drs. Barbara Bates and Robert Hoekelman in 1974, topics relating to the physical examination and the clinical interview have served as the core content of the textbook for teaching and learning clinical skills. The thirteenth edition marks a significant expansion of the scope of the textbook to include the remaining critical components and features of the clinical encounter and now comprises 27 chapters. As authors, we remain committed to providing you with the critical concepts and frameworks you will need to understand and retain material as you encounter abundant new evidence supporting the techniques of examination, interviewing, health promotion, and disease prevention"-- Provided by publisher
International edition.
Includes bibliographical references and index.
Keywords: Periodic health examination; Medical history taking; Physical Examination methods; Medical History Taking methods